Age-specific diastolic dysfunction improves prediction of symptomatic heart failure by Stage B heart failure - Coller, J.M.; Gong, F.F.; McGrady, M.; Jelinek, M.V.; Castro, J.M.; Boffa, U.; Shiel, L.; Liew, D.; Stewart, S.; Krum, H.; Reid, Christopher; Prior, D.L.; et al. (WILEY PERIODICALS, INC, 2019)
Aims: We investigated whether addition of diastolic dysfunction (DD) and longitudinal strain (LS) to Stage B heart failure (SBHF) criteria (structural or systolic abnormality) improves prediction of symptomatic HF in participants of the SCReening Evaluation of the Evolution of New Heart Failure study, a self-selected population at increased cardiovascular disease risk recruited from members of a health insurance fund in Melbourne and Shepparton, Australia. Both American Society of Echocardiography and European Association of Cardiovascular Imaging (ASE/EACVI) criteria and age-specific Atherosclerosis Risk in Communities (ARIC) study criteria, for SBHF and DD, and ARIC criteria for abnormal LS, were examined.